Thermal Conductivity of Papua New Guinea Balsa Wood Measured using the Needle Probe Procedure - Nathan James Kotlarewski; Barbara Ozarska; Benson K. Gusamo (BioResources, 2014)
A study was undertaken with the aim to determine thermal properties of balsa wood grown in plantations in Papua New Guinea. Thermal conductivity values were measured using the needle probe procedure according to ASTM D5334 (2008). The mean thermal conductivity results of balsa were in the range of 0.0381 W/mK to 0.0665 W/mK, similar to other materials currently used as insulators in the construction industry. A balsa sample with a density of 113 kg m3 had the lowest thermal conductivity value, 0.0339 W/mK, across the tangential and radial wood grain directions. Balsa is exported from Papua New Guinea mostly as end-grain panels to international markets to optimise its strength properties in the axial direction for applications that are exposed to compressive forces. This study revealed that there is the opportunity for Papua New Guinea balsa processors to consider producing perpendicular-grain panels for insulation markets, as the mean thermal conductivity values in this direction can be as low as 0.0381 W/mK, which is much lower than the thermal conductivity of the current end-grain panels at 0.0665 W/mK. The finding creates a potential design opportunity for balsa processors to consider entering new commercial markets to promote Papua New Guinea-grown balsa.